Use of sodium taurocholate to enhance spore recovery on a medium selective for Clostridium difficile. - Wilson, K H (1982)
Isolation of Clostridium difficile from fecal specimens has been facilitated by the development of a selective and differential medium, cefoxitin-cycloserinefructose agar (CCFA). We substituted 0.1% sodium taurocholate for the 2.5% egg yolk in CCFA and compared the growth of 15 isolates of C. difficile on the resulting medium with growth on conventional CCFA. The taurocholate-containing medium (TCCFA) quantitatively recovered vegetative forms of C. difficile in the same numbers as CCFA medium. Recovery of spores was a mean 1.7 log(10) higher on TCCFA than on CCFA. Thirty-six of 60 patient stool specimens growing C. difficile gave a heavier growth on TCCFA than on CCFA, and 9 failed to yield C. difficile on CCFA. TCCFA detected spores of 75 colony-forming units per ml from artificially inoculated fecal specimens when conventional stool culturing techniques were used. Fluorescence of colonies of C. difficile was more intense on TCCFA than on CCFA. TCCFA was simpler to prepare and, overall, was more sensitive than CCFA.